2018
DOI: 10.1111/1467-6427.12222
|View full text |Cite
|
Sign up to set email alerts
|

Introducing client feedback into marriage and family therapy supervision: a qualitative study examining the transition to empirically informed supervision

Abstract: The use of client feedback in clinical supervision provides a way for supervisors to access clients' experiences of the treatment process and monitor clinical progress of their trainees' cases. The present qualitative study investigated a marriage and family therapy training programme's early experience of introducing the Systemic Therapy Inventory of Change (STIC®; Pinsof et al., 2009) into clinical supervision. Supervisors (N = 8) and trainees (N = 14) were interviewed to elicit their experience using the ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(48 reference statements)
0
4
0
1
Order By: Relevance
“…Providing a tailored supervision according to client’s progress and outcome data may be an efficacious supervision intervention given that specific presenting concerns can be localized and targeted more effectively in therapy. On the other hand, a qualitative study by McComb, Diamond, Breunlin, Chambers, and Murray (2019) found that additional time needed to incorporate a client feedback system actually led to decreased usage, and Grossl, Reese, Norsworthy, and Hopkins (2014) found that there were no significant differences in clients’ treatment outcome between feedback supervision and supervision-as-usual conditions. Despite the potential, it seems that constraints of implementation and intervention refinements must be addressed for practical impact.…”
Section: Discussionmentioning
confidence: 99%
“…Providing a tailored supervision according to client’s progress and outcome data may be an efficacious supervision intervention given that specific presenting concerns can be localized and targeted more effectively in therapy. On the other hand, a qualitative study by McComb, Diamond, Breunlin, Chambers, and Murray (2019) found that additional time needed to incorporate a client feedback system actually led to decreased usage, and Grossl, Reese, Norsworthy, and Hopkins (2014) found that there were no significant differences in clients’ treatment outcome between feedback supervision and supervision-as-usual conditions. Despite the potential, it seems that constraints of implementation and intervention refinements must be addressed for practical impact.…”
Section: Discussionmentioning
confidence: 99%
“…The use of structured questionnaire reduces the risk of therapists over‐estimating client progress and prevents treatment failure through monitoring and feedback in clinical practice as found by Lambert ( Involving the Chan family in a writing process post treatment further enhances feedback as it allowed the family to have a reflective space to consolidate and appreciate the changes that occurred and were sustained post treatment. Future papers could examine the use of SCORE‐15 in clinical supervision to facilitate treatment outcome and assure treatment quality as argued by McComb, Diamond, Breunlin, Chambers, and Murray () and Lappan et al. ().…”
Section: Resultsmentioning
confidence: 99%
“…Para evaluar la supervisión, se ha empleado el Supervision Personalisation Form (SPF) y el Supervision Personalisation Form-Assessment (SPF-A) (Wallace & Cooper, 2015). En el contexto de la terapia sistémica, se ha estudiado el Inventario de Cambio de Terapia Sistémica para evaluar su uso en supervisión por parte de los supervisores en la evaluación del efecto de la intervención de los supervisados (McComb et al, 2019).…”
Section: Instrumentosunclassified